(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف هذا البحث إلى التعرف على أثر الخبرات الصادمة التي تعرض لها طلاب الصف السادس الأساسي النازحين في محافظة اللاذقية على ظهور أعراض الصدمة النفسية لديهم. نفذ البحث بالاعتماد على مقياس الخبرات الصادمة ومقياس أعراض الصدمة النفسية وكليهما من إعداد الباحثة، وجرى تنفيذ البحث في مدارس التعليم الأساسي في محافظة اللاذقية، وتألفت عينة البحث من (196) طالباً وطالبة في الصف السادس الأساسي، وتوصلت الدراسة إلى عدد من النتائج أهمها: 1- توجد فروق ذات دلالة إحصائية عند مستوى دلالة(0.05) بين المقيمين والنازحين من طلاب الصف السادس الأساسي في الخبرات الصادمة، والفروق لصالح النازحين حيث بلغ متوسط النازحين على مقياس الخبرات الصادمة(15.52) في حين بلغ متوسط المقيمين(11.84). 2- يوجد ارتباط ذو دلالة معنوية عند مستوى دلالة(0.05) بين الخبرات الصادمة التي تعرَّض لها طلاب الصف السادس الأساسي النازحين وأعراض الصدمة النفسية لديهم. This research aims to identify the impact of traumatic experiences suffered by the sixth grade students displaced in the province of Latakia on the emergence of symptoms of psychological trauma they have. search based on a scale traumatic experiences and the measure of symptoms of psychological trauma, which is prepared by the researcher, was carried out in basic education schools in the province of Latakia, consisted on a sample of (196) students in the sixth grade, and the study reached a number of conclusions, including: 1 - There were statistically significant differences at the( 0.05) level of significance between the resident and displaced students from the sixth grade in traumatic experiences, and the differences in favor of displaced persons as the average on a scale traumatic experiences for displaced ( 15.52) while the average resident( 11.84). 2 - There is a significant correlation at the (0.05) level of significance between traumatic experiences that exposure of her sixth-grade students displaced and basic symptoms of psychological trauma they have